Hubungan Berpikir Komputasi dan Pemecahan Masalah Polya pada Pembelajaran Matematika di Sekolah Dasar - Ajeng Rara Veronica; Tatag Yuli Eko Siswono; Wiryanto Wiryanto (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2022)
This study explores the relationship between computational thinking and Polya's problem-solving in mathematics learning. This research is a library research study. The research stages consist of collecting data through books, national journals, and international journals, reducing data, presenting data, and making conclusions. This study is important to do because computational thinking and problem-solving are skills that are very crucial and needed in the era of society 5.0. Both abilities are very important to be developed in learning mathematics, especially in elementary school. Even so, there is little attention to developing computational thinking skills in mathematics learning. Computational thinking and Polya's problem-solving are two interrelated things. In computational thinking, problem understanding occurs in abstraction, decomposition, algorithmic thinking, evaluation, and generalization. The problem-solving planning process occurs in abstraction and decomposition. The implementation of the solution plan occurs in algorithmic thinking and evaluation. Meanwhile, a re-examination occurs in the evaluation and generalization aspects.